The Effect of Serial Image Media on Students’ Skill in Writing Descriptive Essays - Dede Zulfa Sania; Ade Hikmat (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2023)
Lack of media used by teachers so far needs to be changed. It is intended that students are not only of high theoretical quality but also of high practical quality. The purpose of this study is to find out the effect of series image media on the writing skills of grade III students of Madrasah Ibtidaiyah (MI) Al-Ikhlasiyah, Depok. In this study there were populations, namely all students in class III A and III B with a sample of 40 students. In this study, the data collection technique used the pretest posttest. The data analysis technique used was Normality and Homogeneity tests. The results of the analysis of research data stated that the existence of a series of media images was very affect with the ability to write descriptive essays for grade III students of MI Al-Ikhlasiyah, Depok. This was seen based on the average score of pretest and posttest results that have been carried out in the experimental group and the control group. The average pretest score obtained by the experimental group was 69, and for the control class the average score was 67.75. After both classes received treatment, the experimental class obtained an average score of 80.75 while for the control class obtained an average of 76.00. The same as the results of calculations through the t-test. The calculation results in the experimental group resulted in a probability value of <0.05, which is 0.000, which means that the series image media affect student learning outcomes.